2002
DOI: 10.1079/bjn2001485
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, brain development and scholastic achievement of Chilean high-school graduates from high and low intellectual quotient and socio-economic status

Abstract: The objective of the present study was to investigate the inter-relationships between nutritional status (past and current nutrition), brain development, and scholastic achievement (SA) of Chilean high-school graduates from high and low intellectual quotient (IQ) and socio-economic status (SES) (mean age 18 : 0 (SD 0 : 9) years). Results showed that independently of SES, highschool graduates with similar IQ have similar nutritional, brain development and SA variables. Multiple regression analysis between child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
66
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 62 publications
(77 reference statements)
9
66
0
6
Order By: Relevance
“…Other results demonstrated that independent of socio-economic stratum, children older for grade have a significantly lower intellectual quotient and scholastic achievement (SA), decreased brain parameters, a deprived nutritional status and a higher course repetition rate (Ivanovic et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other results demonstrated that independent of socio-economic stratum, children older for grade have a significantly lower intellectual quotient and scholastic achievement (SA), decreased brain parameters, a deprived nutritional status and a higher course repetition rate (Ivanovic et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other findings point out that independent of socio-economic stratum, sex and age, maternal intellectual quotient or maternal schooling, brain volume and undernutrition in the first year of life are the main determinants of intellectual quotient and this in turn is the most relevant parameter that explains SA (Ivanovic et al, 2000a(Ivanovic et al, , b, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…8 Other studies have shown that small head circumference at birth can also predict poor intellectual performance in childhood and adulthood, 9,10 although this relationship appears to depend on the particular cognitive domain. 11 Head circumference is considered the most sensitive anthropometric measure of long-term malnutrition in infancy, 12,13 with caloric deprivation shown to be directly associated with suboptimal head growth. 14 Among small-for-gestational age preterm infants, higher mean postnatal energy intake/kg body weight per day in the first 2 weeks of life was associated with complete head circumference catch-up growth and better developmental and cognitive performance until the age of 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from Brazil and Peru document a lasting impact of diarrhea (as with malnutrition and intestinal helminthic infections) on child development with ill-effects on cognition, growth, and educational performance [2,3]. Early post-natal malnutrition is associated with significantly retarded central nervous system growth, reduced brain weight, thinner cerebral cortex, deficient myelinization, poor neuritic arborization, and changes in features of dendritic spines such as reduction in their width and number [4][5][6].…”
Section: Introductionmentioning
confidence: 99%